The value of telepharmacy – current costs and future savings - Lakić, Dragana (Archives of Pharmacy, 2022)
Combination of information and communication technology in provision of pharmaceutical care provides possible solution in the era of health professional shortage and increased costs. Telepharmacy involves services such as medication selection, order review, dispensing, compounding, drug information services, patient counseling, and medication monitoring, offered to the patients located at the distance. Increasing evidence suggests possible clinical benefits of telepharmacy such as the easy access to healthcare services, especially in remote and rural communities, increased patient satisfaction as a result of medication access in rural areas, effective patient counseling, reduction in adverse drug events, decrease rate of dispensing errors and better documentation of pharmacist interventions. However, telepharmacy can be sometimes challenging to put into practice. The start-up of telepharmacy (hardware, software, technological infrastructure, internet connection, and operational cost) can be significant financial burden and time-consuming activity. The initial investment can be substantial either to the individuals or to the health system. Even in addition to this initial investment, literature shows that the development of telepharmacy services is cheaper than to open new pharmacies. Clinical benefits, mainly avoidance of adverse drug events and dispensing errors, can be translated into the possible future savings. Besides that, the introduction of telepharmacy can bring to a reduction of pharmacy services costs as with this technology one pharmacist can cover multiple sites and a wider area. Telepharmacy also allows patients to save money and travel time.